THE EFFECTIVENESS OF ISLAMIC FINANCE INSTRUMENTS OF THE SHARIA BANK “X” JAWA TENGAH, INDONESIA - Riswan Riswan (Universitas Tidar, 2017)
This study aims to evaluate the level ef effectiveness of the Islamic financial instruments at The Sharia Bank “X” Jawa Tengah, Indonesia in term of: firstly, fund utilizing management instruments of Islamic assets, secondly, the liquidity management instruments of Islamic liabilities, and thirdly, the Sharia governance framework. Implementing decriptive analysis through questionnaire distribution to the respondents with purposive sampling during OctoberNovember 2016 period, the findings show that fund utilizing management instruments of Islamic assets is moderately effective, the liquidity management instruments of Islamic liabilities is effective, and the Sharia governance framework is effective.Keywords, Islamic assets, Islamic liabilities, Sharia governance framework